Valuation of the Reliability of the Formulas of the Yo-Yo Intermittent Recovery Test (Level 1) and 30-15 IFT, which are Intermittent Endurance Tests Used to Determine Maximum Oxygen Capacity - Nurettin Ersin Uzun; Tuba Kızılet Bozdoğan; Ali Kızılet (ümit doğan üstün, 2021)
For athletes to perform high-intensity movements with high quality, anaerobic endurance must be developed in order to repeat these movements one after the other with the same quality and without fatigue. Aerobic and anaerobic endurance characteristics should be followed by using tests suitable for the requirements and structure of the sports branch before and during the season. The aim of this study is to determine the maximal oxygen consumption (MaxVo2) with indirect MaxVo2 values ​​obtained with the help of formulas from "Yo-yo Intermittent Recovery Test (level 1) (YATT1)" and "30-15 Intermittent Endurance Test (30-15 IFT)". The purpose of this study is to compare the direct MaxVo2 value determined by using an oxygen analyzer in these tests and to examine the reliability of the formulas. The sample group of the study consists of 12 male athletes with an average age of 21.7 ± 1.2 who play futsal and badminton licensed in Marmara University Faculty of Sports Sciences. MaxVo2 values ​​of the athletes were determined indirectly by putting the test result into the test formula, and directly by the oxygen analyzer on the athletes during the test. According to the results of the study, a correlation was determined between direct and indirect measurement methods according to the results of the correlation test of the data obtained from YATT1 and 30-15 IFT (respectively; 828**, p=0.001 and 816** p=0.001). According to the results of the co-sample t-test performed for the measurement methods themselves, a statistically significant difference was found between the two measurement methods (p= 0.002 and p=0.019, respectively). Finally, while there was no statistically significant difference between direct measurements of YATT1 and 30-15 IFT (p=.454), a statistically significant difference was found between indirect measurements (p=0.002). According to the results of the study, it is appropriate to use both direct and indirect measurement methods of YATT1 or 30-15 IFT tests, considering the sport-specific features, in determining MaxVo2.